Does light pollution affect nighttime ground-level ozone concentrations? - Shith, Syabiha; Ramli, Nor Azam; Awang, Norrimi Rosaida; Ismail, Mohd Rodzi; Latif, Mohd Talib; Zainordin, Nazatul Syadia (MDPI, 2022)
Ground-level ozone (O3) is mainly produced during daytime in the presence of ultraviolet (UV) light and later destroyed by nitrogen oxides during nighttime. However, light pollution caused by the excessive use of artificial lights may disrupt the chemistry of night-time ground-level O3 by providing enough energy to initiate nighttime ground-level O3 production. In this study, nighttime (7 p.m. to 7 a.m.) ground-level O3, nitrogen oxide (NO), and nitrogen dioxides (NO2) concentrations were observed for three years (2013, 2014, and 2015). The existence of O3 was found during nighttime, especially in urban areas with a concentration range of 8–20 ppb. The results suggested that nighttime variations of ground-level O3 concentrations were higher in urban areas than in suburban areas. The mean nighttime O3 concentration at urban sites varied, possibly because the distribution of anthropogenic lights around the urban sites is brighter than in suburban locations, as indicated by the data from the light-pollution map. This anthropogenic light has not caused the suspected nighttime photolysis processes, which directly slowed nighttime oxidation. The photochemistry rate of JNO2/k3 was supposed to be near zero because of the absence of photochemical reactions at night. However, the minimum concentration in all urban and suburban sites ranged from 2–3 ppb, indicating that O3 might also form at night, albeit not due to light pollution.